Association between Serum Uric Acid Levels and Diabetes Mellitus - Pavani Bandaru; Anoop Shankar (2011)
Serum uric acid has been shown to be associated with cardiovascular disease, hypertension, and chronic kidney disease in previous studies. However, few studies have examined the association between serum uric acid and diabetes mellitus and their findings are not consistent. Therefore, we examined the association between serum uric acid levels and diabetes mellitus in participants from the third National Health and Nutrition Examination Survey (, 52.5% women). Serum uric acid levels were categorized into quartiles. Diabetes mellitus was defined as fasting glucose ≥126 mg/dL, nonfasting glucose ≥200 mg/dL, or use of oral hypoglycemic medication or insulin (). In multivariable logistic regression models, we found that higher serum uric acid levels were inversely associated with diabetes mellitus after adjusting for age, sex, race/ethnicity, education, smoking, alcohol intake, body mass index, hypertension, and serum cholesterol. Compared to quartile 1 of serum uric acid, the odds ratio (95% confidence interval) of diabetes mellitus was 0.48 (0.35–0.66; trend ). The results were consistent in subgroup analysis by gender and hypertension status. Higher serum uric acid levels were inversely associated with diabetes mellitus in a representative sample of US adults.